Phenology of Sclerocarya birrea (A. Rich.) Hochst. Provenances - V. J. Msukwa; C. R. Y. Munthali; B. I. Nyoka; E. Missanjo (Ital Publication, 2019)
Phenology study was conducted to assess 22 genotypes of Sclerocarya birrea (A. Rich.) Hochst, collected from West, Eastern and Southern Africa. Assessments were done on time for bud onset, flower opening, leaf flush, fruit set, fruit maturity period and fruit production. Highly significant (P< 0.001) variations between provenances were obtained in all the phenological traits assessed including variations between sexes in time from flower bud set to anthesis. There was flowering overlaps and synchrony between provenances and sexes with males flowering earlier than females. So far two subpopulations have emerged within the trial referred to as early and late flowering genotypes. The early flowering included provenances from Mozambique, and Swaziland while the late flowering encompassed provenances from Malawi, Zimbabwe, Namibia, Tanzania and Zambia. Fruit maturity period ranged from 76±2 to 192±15days. The early flowering genotypes flowered, fruited and matured between August and January while the late genotypes flowered and fruited from September to May. There were highly significant (P≤0.001) variations in fruit yield of S. birrea provenances between 2016/2017 and 2017/2018 seasons with the former being more productive than the later confirming that S. birrea fruit yield is not constant across seasons due to seed mating effects. There were very strong positive relationship ranging r=0.81 to r=0.78 between leaf flush, bud set, flower opening and fruit set significant at (P<0.001). Some trees classified as females in the first year as based on flowers were found have male flowers which calls for more detailed investigations into this sex change behaviour.